Primary micro cystic urothelial carcinoma of urinary bladder: A rare variant managed conservatively - Varinder Attri; Kalpesh Parmar; Abhishek Choube; Pulkit Rastogi (Elsevier, 2020)
The urothelial cancer variants are usually high grade and carry poor prognosis. Glandular neoplasm of urothelium is uncommon and cystic differentiation in such tumours demonstrate multiple cystic spaces in the nest of the urothelium. These cases represent less than 1% of variants. We present one case of microcystic variant of urothelial cancer in a 60-year old postmenopausal female managed conservatively with transurethral resection of bladder tumor (TURBT) and intravesical BCG instillation and currently is disease free.